Barely visible impact damage in scaled composite laminates: Experiments and numerical simulations. (November 2017) - Sun, X.C.; Hallett, S.R.
Highlights: The work presented here investigated the low-velocity impact damage resistance of ply level and in-plane level scaled composite laminates using detailed experiments and numerical modelling. It demonstrated the robustness of previously developed high-fidelity solid finite element modelling technique in a dynamic impact environment. An efficient Solid/shell modelling technique was developed with capabilities of predicting impact damage of large and complex composite structures with reasonable computational cost, and the modelling results were systematically validated through highly detailed testing. Abstract: This paper investigates the effect of size and complexity of composite structures on the formation of low-velocity impact damage via experimental tests and numerical modelling. The ASTM standard low-velocity impact test and a scaled-up version of the test were conducted. A novel numerical technique is presented that combines 3D solid and thin 2D shell elements for modelling different domains to achieve a high level of fidelity locally under the impact location, whilst achieving good computational efficiency for large structures. Together with the experimental studies at the different scales, the predictive capability of the numerical models was systematically validated. This modelling method demonstrated an advanced computational efficiency without compromising predictive accuracy. The models are applied to a case study of low-velocity impact of a large-scale stringer-stiffened panel, showing this modelling approach to be suitable for predicating low-velocity impact damage and structural response of laminated composites over a range of sizes and complexities.